Performer son sexe - Hélène Martin; Rebecca Bendjama; Raphaëlle Bessette-Viens (Glad!)
This article explores and analyses the discourse presented on clinics’ and doctor’s offices’ websites that promote genital improvement surgeries in French-speaking Switzerland. Paying particular attention to power relations and to the articulation of the biological and the social, it aims at understanding how genitals and sexuality are presented. Using an analysis based on the identification of discursive processes and lexical fields, the authors identify three main themes : the promotion of sexual fulfillment and two types of obstacles understood as preventing its achievement. These obstacles are, on the one hand, innate or acquired morphological abnormalities and, on the other hand, discourses and practices considered oppressive and of a ‘cultural’ nature. The article develops the idea that, through the imperative to ‘become our true selves’, gender, culture and class intersect with the process of individualization of social norms.